Motivasi, Kompensasi, dan Kepuasan Kerja terhadap Kinerja Karyawan - Dharni Yanti Telaumbanua; Riama Silaban (IPM2KPE, 2022)
This study aims to determine the effect of motivation, compensation, and job satisfaction on employee performance at PT. One Family Medan Branch. This research method is descriptive quantitative. In this study the population used at the company PT. One Family Medan Branch as many as 40 employees. Data processing using SPSS application. The results showed that the motivation variable had a positive and significant effect on employee performance with a significance of 0.046 and tcount of 2.160. The compensation variable has a positive and significant effect on employee performance with a significance of 0.03 and tcount of 3.489. Job satisfaction variable has a positive and significant effect on employee performance with a significance of 0.001 and a tcount of 4.255. In conclusion, the variables of motivation, compensation, and job satisfaction have an effect on employee performance. Keywords: Job Satisfaction, Performance, Compensation, Motivation